Effect of Guano Fertilizer Doses and Atonic Concentrate Growth Regulator Substances on Curly Chili (Capsicum annum L.) Plant Yields - Arifa Bingar Mulia; Djarwatiningsih Pongki Soedjarwo; Didik Utomo Pribadi (Nusantara Science and Technology Proceedings, 2023)
Curly chili (Capsicum annum L.) is a horticultural plant that is included in the vegetable commodity. Production of curly chilies in Indonesia is still unstable so the need for curly chilies is not met so production needs to be increased. This research aimed to determine the effect of the optimal dose of guano fertilizer and concentration of the Atonik Growth Regulator on the yield of curly chili plants The research location is on cultivated land of the Faculty of Agriculture, Universitas Pembangunan Nasional “Veteran” Jawa Timur. This research used a factorial experiment which was prepared using a Completely Randomized Design consisting of 2 factors. The first factor is the dose of guano fertilizer (G) consisting of G0: control, G1: 30 g / polybag, G2 : 60 g / polybag, and G3 : 90 g / polybag. The second factor is the atonic ZPT concentration consisting of A0: control, A1: 2 cc/liter, and A2: 4 cc/liter. Observation indicators consist of observations of the vegetative and generative phases. Research data will be analyzed using variance (ANOVA) and if it is significantly different it will be tested further using the Least Significant Difference (BNT) at the 5% level. The results of the research showed that the application of guano and atonic fertilizers affected the yield of curly chili plants with the most effective combination being a dose of guano fertilizer of 90 g/polybag and an atonic concentration of 4 cc/liter.